The Effect of Halal Awareness and Halal Labels on Consumer Preferences in Shopee E-Commerce: Case Study of Shopee Users in Belawan Sicanang Village - Raza Fari Jiranda; Salman Nasution (Newinera Publisher, 2024)
This study aims to understand the impact of Halal Awareness and Halal Label on Consumer Preferences in the Shopee E-commerce Platform: A Case Study of Shopee Users in the Belawan Sicanang District. The research employs a quantitative approach. Data collection was conducted by distributing questionnaires and using a Likert scale to measure respondents' responses. The study involved 94 respondents selected through purposive sampling. Multiple regression analysis was used for data analysis using SPSS version 26.